INDONESIA’S DEFENSE HEALTH PERSPECTIVE - Soroy Lardo (Jurnal Pertahanan: Media Informasi ttg Kajian & Strategi Pertahanan yang Mengedepankan Identity, Nasionalism & Integrity, 2019)
The National Defense System is a systematic and planned concept, structure and organization, fostering the spirit of the universe of the people and nation, to strengthen and defend themselves from various threats, challenges, obstacles and disturbances that break the Indonesian building and network. The concept embodies software that contains the philosophy, purpose, theoretical framework and framework of the concept of national defense, as a soul and heart that moves continuously in the spirit of conscience defending the country. The purpose of this study is to develop a study about the strategic role of defense health as a diversified potential for multifunctional health to guide the national level of resilience. The potential of health in the field of defense with its strategic thinking decomposes the breadth of Indonesia's geographic region, which has distinctive characteristics of health problems based on geomedicine maps. The dynamic stratification of health problems makes geomedicine maps as a measure of defense health policy. The concept proposed in this study is expected to be one of the basic references in forming a defense health study program at Indonesia Defense University. The method, that needs to be developed, is the transformation of the health of Indonesian National Armed Forces (TNI). At this time, it has achieved dynamic values in realizing a broader role, not only in the field of health services and support, but it has begun to expand into the field of research and development (R & D). This development also related to global challenges, where the spread/pandemic of illness becomes an extraordinary homework, especially related to defense health. Defense health is a multiparadigmatic concept with multidisciplinary scientific dimensions and parameters, and various multi-approaches (analysis, synthesis, and solution), based on philosophy and history, build a defense health characteristic that has a scientific perspective that has reliability and validity, so th purpose of this study can be obtained.